Rekomendasi Pemilihan Peserta Lomba Kompetensi Siswa (LKS) Tingkat Kejuruan Dengan Teknik Promethee - Andi Sahputra; Eka Irawan; Harly Okprana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Participants in the student competency competition (LKS) of the RK Bintang Timur Pematangsiantar Private Vocational School were conducted manually by collecting students, counting and comparing with supporting data such as competency report cards by productive teachers. Therefore the RK Bintang Timur Pematangsiantar Private Vocational School needs to overcome problems in selecting students as participants in the student competency competition to be more effective and on target. The Promethee algorithm is used in order of order or priority in an efficient and simple multi-criteria analysis. Based on the research data sample, the highest score was obtained in alternative A1 with a value of 0.406 with 6 criteria, namely academic value, number of absences, student council scores, attitude, craft and tidiness. Then proceed to the matrix normalization process which produces the outflow, inflow and net flow values ??used in the ranking process